Participation of Legal Profession Self-Government Organizations in the Process of Law-Making - Arkadiusz Bereza (Barometr Regionalny, 2019)
Self-governments of legal professionals give their opinions on draft legal acts as part of public consultations and cooperation with the Minister of Justice, based on statutory delegation. The most active in this respect is the self-governments of attorneys-at-law and advocates, to which drafts of all legal acts are being sent. To this end, specialized agencies have been created in these organizations, which carry out the statutory task of self-governments of legal professions to provide opinions on draft legal acts. Since 2016, comments on drafts submitted by legal profession self-governments have rarely been taken into account, and sometimes there is even no evidence for a more profound analysis thereof. This means that there is no reliable consultation, which undoubtedly affects the quality of law. This is the result of a fast and too much simplified legislative process that dominated the period of 2016–2018.